Fabrication of Bioactive Coatings on Steel Substrates by Electro-Spark Deposition (ESD) and Micro-Arc Oxidation (MAO) Methods - Yilmaz, M. S.; Cakir, A.; Ribalko, A.; Korkmaz, K. (Polish Acad Sciences Inst Physics, 2015)
In the present study, first Ti6Al4V alloy was deposited on steel (AISI 1060) surfaces by using ESD method. The optimum electrical parameters for the coating process were investigated to obtain high quality coatings. Then, in order to gain bio-compatibility and obtain second layer, which was coated with hydroxyapatite (HAp), MAO technique was applied on the present coating. Resulting duplex layers were characterized with X-ray diffraction (XRD) and scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDX) analysis together with surface roughness, coating thickness, scratch tests and hardness tests.
4th International Congress in Advances in Applied Physics and Materials Science (APMAS) -- APR 24-27, 2014 -- Fethiye, TURKEY
Keywords: Surface; Titanium